Polyvinylidene Fluoride/Multiwalled Carbon Nanotubes Membrane For Methylene Blue Dye Removal Via Adsorption - Rajendren, Munesh Daniel (Universiti Sains Malaysia, 2018)
The polyvinylidene fluoride (PVDF) membrane is fabricated by phase inversion method for the adsorption of methylene blue dye from its solution. The functionalized multiwalled carbon nanotubes (MWCNTs) containing carboxylic groups (-COOH) functional groups are incorporated into the PVDF membrane to improve the mechanical strength as well as the adsorption qualities of the membrane. The MWCNTs act as a bridge that would provide more vacant adsorption sites compared to PVDF membrane by itself to assist in the adsorption of the methylene blue dye. The adsorption process is then tested with 3 different factors which are temperature, contact time and the initial concentration of the methylene blue (MB) dye solution to observe which factors affect the PVDF as well as the PVDF/MWCNT membrane most. The study of the effect of temperature showed that the efficiency of the adsorption decreases as the temperature of the mixture increases. This leads to the conclusion that the adsorption process between PVDF as well as PVDF/MWCNT and the MB dye is an endothermic process. The study of the contact time between the membrane and the MB dye showed that the process begins rapidly when the concentration of the solution decreases by 5.66% in the first hour and slowly reduces in efficiency when the concentration only reduced about 2% over the next 3 hours due to the vacant adsorption sites being filled. The study of the initial concentration of MB dye solution revealed that both PVDF and PVDF/MWCNT membrane is able to accommodate MB dye solution of 1-2 mg/l without loss of efficiency. The PVDF membrane starts losing efficiency at MB dye concentration of 3 mg/l whereas PVDF/MWCNT membrane starts losing efficiency at MB dye concentration of 4 mg/l. The study of the adsorption isotherms showed that the best fit isotherm for the adsorption process between the PVDF and PVDF?MWCNT membrane with the methylene blue solution would be the Langmuir isotherm.